2007
DOI: 10.5194/acp-7-5357-2007
|View full text |Cite
|
Sign up to set email alerts
|

Medium-range mid-tropospheric transport of ozone and precursors over Africa: two numerical case studies in dry and wet seasons

Abstract: Abstract.A meso-scale model was used to understand and describe the dynamical processes driving high ozone concentrations observed during both dry and monsoon season in monthly climatologies profiles over Lagos (Nigeria, 6.6 • N, 3.3 • E), obtained with the MOZAIC airborne measurements (ozone and carbon monoxide). This study focuses on ozone enhancements observed in the upper-part of the lower troposphere, around 3000 m. Two individual cases have been selected in the MOZAIC dataset as being representative of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…The similar magnitude of the ozone underestimation and lightning source (0.061 TgN) in our CHASER simulation shows that although the global total lightning source is similar for our simulation (7.5 TgN yr −1 ) and estimates from chemical observations (mostly 6-8 TgN yr −1 ) (e.g. Martin et al, 2007;Sauvage et al, 2007), CHASER may underestimate lightning NO x sources and their-induced ozone production in the free troposphere over Mexico and North America. Errors in the stratospheric ozone transport into the troposphere may also contribute to the ozone underestimation.…”
Section: Europementioning
confidence: 56%
“…The similar magnitude of the ozone underestimation and lightning source (0.061 TgN) in our CHASER simulation shows that although the global total lightning source is similar for our simulation (7.5 TgN yr −1 ) and estimates from chemical observations (mostly 6-8 TgN yr −1 ) (e.g. Martin et al, 2007;Sauvage et al, 2007), CHASER may underestimate lightning NO x sources and their-induced ozone production in the free troposphere over Mexico and North America. Errors in the stratospheric ozone transport into the troposphere may also contribute to the ozone underestimation.…”
Section: Europementioning
confidence: 56%
“…According to Sauvage et al (2007b), these vertical winds are primarily caused by surface gradients in temperature and humidity, with the warm dry surface being located poleward and the cooler wet surface equatorward of the ITF. Furthermore, based on a case study, Sauvage et al (2007b) have shown that during the WAM, the low-level circulation induced by these surface gradients is responsible for the uplift of biomass burning pollutants to the level of the African Easterly Jet (∼600 hPa), which results in their long-range transport to Western Africa. The large scale UT circulation is characterised by the presence of thermally induced anticyclones over low-latitudes continental regions (Hastenrath, 1991).…”
Section: Aura/mls Observations Of O 3 and Co In The Utlsmentioning
confidence: 99%
“…The Harmattan winds become stronger and move equatorward near 700 hPa, and merge with the southeasterly trade winds around 5 • N. There is a region of strong upward mass fluxes in the MT (430 hPa) primarily north of the Equator that lofts CO from the fires to the MT and UT. Several studies discuss these transport pathways during the West Africa monsoon season, in the context of interpreting ozone and CO observations (Sauvage et al, , 2007a, including MLS CO data (Barret et al, 2008(Barret et al, , 2010. Barret et al (2008) attribute the CO maximum over northern Africa at 215 hPa (in July 2006) mainly to convective uplift of CO-rich air from biomass burning in southern Africa following these transport pathways.…”
Section: Southern Africamentioning
confidence: 99%